Bezier Curve Interpolation On Road Design - Saffie, Mohd Syakir (2019)
This research focuses on reconstructing the road curve by using Bezier curve fitting on a map. The usual way of constructing the Bezier curve is by using control points which can be very tedious. Since Bezier curves do not interpolate the control points, designers need to estimates the position of control points so that the curve fits well. In order to ease up the process, we will construct the Bezier curve by using the parameterization method where the data point information is required instead of the usual way of using control points. However, this method does not work on Bezier curve of high degree as the curves tend to become perturbed. One way of solving the problem is by using piecewise Bezier curve made up of several parameterized Bezier curves of lower degree. We propose a method to satisfy the continuity properties along this piecewise parameterized Bezier curve. The method had been implemented on two-dimensional model and spatial model. By using this method, we manage to construct a Bezier curve that can interpolate high number of data points while satisfying the continuity properties along the curve.